Penerapan Model Pembelajaran Flipped Classroom pada Siswa Kelas X SMAN 2 Lubuk Sikaping terhadap Hasil Belajar Materi Perubahan Iklim - Ratih, Nofia; Nerita, Siska; Zural, Mimin Mardhiah (Biocaster : Jurnal Kajian Biologi, 2025)
This study is motivated by the low learning outcomes of students due to lack of active participation in group discussions and questions and answers, so that the understanding of the material is not optimal. This study aims to determine student learning outcomes with the application of flipped classroom in grade X students of SMAN 2 Lubuk Sikaping on climate change material. This type of study is an experiment with a randomized control group posttest-only design. The research population is all students of class X Phase E of SMAN 2 Lubuk Sikaping in the even semester of the 2024/2025 academic year. The research sample was class X E3 as the experimental class and X E7 as the control class selected by purposive sampling technique. The research instrument is in the form of a multiple-choice test. Data analysis techniques include normality tests, homogeneity tests, and hypothesis tests (t-tests). The results of the study show that the application of flipped classroom provides a significant increase in student learning outcomes on climate change materials.